Pemberdayaan Kelompok Wanita Tani (KWT) di Desa Tawang melalui Pelatihan Pembuatan Pupuk Organik Cair dari Gedebog Pisang - Wijayanto, Danar Susilo; Aprilya, Kartika; Firdaus, Safira; Muthi, Annisa Salsabila Ghina; Amanda, Attala Surya Prima; Thoriq, Khaira Fadia; Amanda, Kristina Dwi; Yuari, Malik; Ussalam, Naafi’; Putri, Nada Hanifah; Panuntun, Philip Purwoko Adi (DEDIKASI: Community Service Reports, 2023)
Banana stems are organic waste that contains elements that are beneficial to plants. The management of banana stems can be used as liquid organic fertilizer as an effort to reduce the presence of waste and can be used as fertilizer for plants. On this basis, KKN UNS held a training activity on making POC from banana stem which was attended by 50 members of Kelompok Wanita Tani (KWT) in Tawang Village. Training on making POC from banana stem aims to utilize unused waste and provide insight and experience for participants in making POC. Training consists of providing material and direct practice in making POC. The results of the manufacturing practice are used for fertilizer for plants in the garden owned by KWT Tawang Village.